2023
DOI: 10.3389/fcell.2023.1072629
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain: Mechanisms and therapeutic strategies

Abstract: The physiopathology and neurotransmission of pain are of an owe inspiring complexity. Our ability to satisfactorily suppress neuropathic or other forms of chronic pain is limited. The number of pharmacodynamically distinct and clinically available medications is low and the successes achieved modest. Pain Medicine practitioners are confronted with the ethical dichotomy imposed by Hippocrates: On one hand the mandate of primum non nocere, on the other hand, the promise of heavenly joys if successful divinum est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 167 publications
0
5
0
Order By: Relevance
“…Capsaicin is widely used worldwide, but there is ongoing debate about the safety. For example, epidemiological and laboratory data have suggested that capsaicin can act as a carcinogen or anticarcinogen ( 88 90 ). Capsaicin appears to interact with xenobiotic-metabolizing enzymes, particularly microsomal cytochrome P450-dependent monooxygenases, which are involved in activation as well as detoxification of various chemical carcinogens and mutagens ( 1 , 91 , 92 ).…”
Section: Pharmacokinetics Of Capsaicinmentioning
confidence: 99%
“…Capsaicin is widely used worldwide, but there is ongoing debate about the safety. For example, epidemiological and laboratory data have suggested that capsaicin can act as a carcinogen or anticarcinogen ( 88 90 ). Capsaicin appears to interact with xenobiotic-metabolizing enzymes, particularly microsomal cytochrome P450-dependent monooxygenases, which are involved in activation as well as detoxification of various chemical carcinogens and mutagens ( 1 , 91 , 92 ).…”
Section: Pharmacokinetics Of Capsaicinmentioning
confidence: 99%
“…Serotonin (5-hydroxytryptamine, 5-HT) receptors, particularly the 5-HT3 and 5-HT1A subtypes, play a role in pain modulation [ 27 , 28 ]. The 5-HT3 receptor is involved in the transmission of pain signals in the spinal cord [ 29 , 30 , 31 ].…”
Section: Drug Targets In Neuropathic Painmentioning
confidence: 99%
“…In other chronic painful diseases, prognosis, choice of therapy, and treatment response vary according to pain type (nociceptive, neuropathic, and/or nociplastic). 6,54,57,58 Recently published HS pain management algorithms suggest differential treatment according to HS pain type 59 ; however, data supporting the presence of multiple pain types in HS have been based exclusively on survey studies. 7,44,60,61 This study provides additional evidence for the presence of nociplastic and nociceptive pain in HS.…”
Section: Limitations and Clinical Implicationsmentioning
confidence: 99%